The Structural Effects of State Regulation of Retail Fluid Milk Prices: A Reply - Masson, Robert Tempest; DeBrock, Lawrence Marvin (The Review of Economics and Statistics, 1982)
Robert Tempest Masson, Lawrence Marvin DeBrock, The Structural Effects of State Regulation of Retail Fluid Milk Prices: A Reply, The Review of Economics and Statistics, Vol. 64, No. 3 (Aug., 1982), pp. 534-536